Assessment of Malnutrition as a Risk Factor for Acute Lower Respiratory Tract Infection in Children under 5 yr Age at a Tertiary Hospital - Manandhar, Sunil Raja; Thorell, Petter; Kallur, Ida; Joshi, Sunil Kumar (Journal of College of Medical Sciences-Nepal, 2019)
Background: Malnutrition among young children is becoming a major public health concern in low income countries like Nepal where under nutrition remains one of the primary causes of ill health. Acute lower respiratory tract infection (ALRTI) and malnutrition in children are associated with morbidity and mortality in developing countries.Objective of this study was to assess ALRTI as a risk factor for malnutrition in children at Kathmandu Medical College Teaching Hospital. Methods: This was a cross-sectional study con-ducted at Kathmandu Medical College Teaching Hospital over 5 months duration (August - December 2017). Under 5 yrs children diagnosed as ALRTI were taken and healthy children from same age group attending the immunization clinic were the controls. Anthropometric measurements were measured and stunting and wasting were described according to the WHO classification of malnutrition. Data were analyzed using SPSS version 18. Statistical analyses were done in the form of frequency, mean and cross tabulation. Chi-Square test was used to assess the association of ALRTI with malnutrition. P value <0.05 was considered to be sig-nificant. Results: A total of 200 children were included in this study. Children with ALRTI (n = 90) and con-trols (n =110) were analyzed. Male participants were observed more in both groups (60% and 68%). Wasting and stunting were observed more in ALRTI group than in control groups. Conclusions: This study showed there was a relation between ALRTI and malnutrition in children. So, this study has identified malnutrition as one of the major risk factor for ALRTI in under 5 yrs children.